Volatility of Daily Nepal Stock Exchange (NEPSE) Index Return: A Garch Family Models - Dangal, Dil Nath; Gajurel, Ram Prasad (Tribhuvan University Journal, 2021)
The major intend of this study is to investigate the volatility clustering in NEPSE index. To reach the conclusion, 3392 annually observed time series data from 1 June 2006 to 7 April 2021 were obtained from various volume of annual trading report of Nepal Stock Exchange (NEPSE) and website of NEPSE and symmetric Generalized Autoregressive Conditional Heteroscedasticity (GARCH) models––GARCH (1,1), GARCH-M (1,1) and asymmetric GARCH family models––TGARCH (1,1), EGARCH (1,1), and PGARCH (1,1) were employed. The stylized facts confirm that the volatility clustering and leverage effect on the return of NEPSE index are existed. The empirical analysis reveals that the positive correlation between volatility and the expected return of NEPSE index in terms of risk premium and then conditional variance process is persistent. The empirical results also show that the symmetric model is better fitted to full sampled period and asymmetric GARCH family models to before-and after-earthquake sampled period. This study covers the larger dataset which is divided into different episodes with different economic condition of Nepal and thus, it is assumed to be a purely an initial work on Nepalese stock exchange.